Vascular endothelial growth factor gene polymorphisms and age-related macular degeneration in an Egyptian population - Marwa Abdel Kareem Mohamed Aly; Hanan Salah El Deen Mahrous; Lubna Mohamed Ibrahim Desouky; Karim Mahmoud Nabil (Delta Journal of Ophthalmology, 2023)
Purpose The aim of this study was to investigate the role of −1154 guanine (G)>adenine (A) and +405 G>cytosine (C) vascular endothelial growth factor (VEGF) gene polymorphisms as possible risk factors for neovascular age-related macular degeneration (nAMD) and to evaluate their role in patients’ response to anti-VEGF therapy. Patients and methods The study included 50 nAMD patients and 64 age and sex-matched healthy volunteers. Polymerase chain reaction-restriction fragment length polymorphism was performed to assess the VEGF −1154 G>A and +405 G>C polymorphisms in relation to AMD. Results Hypertension was reported in 40 (80%) cases compared to 14 (21.9%) of the controls, with a statistically significant difference (P < 0.001). Heart disease was also reported more significantly in patients (13 = 26%) than in controls (7 = 10.9%), P = 0.036. In addition, smoking was detected in 39 cases (78%) compared to 10 (15.6%) controls, a statistically significant difference (P < 0.001). Molecular analysis of VEGF −1154 G>A and VEGF +405 G>C gene polymorphisms yielded nonstatistically significant difference between cases and control groups. Assessment of genotype frequency of VEGF −1154 among responders and nonresponders yielded nonstatistically significant difference. However, genotype frequency of VEGF +405 among responders and nonresponders revealed a statistically significant difference, with the GG genotype associated with better response to anti-VEGF therapy (61.1% responders versus 28.6% nonresponders according to visual acuity and optical coherence tomography parameters, P = 0.037). Conclusion Smoking, hypertension, and heart disease were critical risk factors for the development of AMD. The VEGF +405 G>C genotype was found to be an important predictor for response to anti-VEGF therapy.